Pengaruh Inflasi, BI rate, dan Kurs Dollar/rupiah Terhadap Indeks Harga Saham Gabungan (IHSG) Periode 2012-2016 - Lim, Yulius B1021131009 (Jurnal Manajemen Update, 2018)
This study is about how inflation, BI rate, and dollar/rupiah rate effect to composite stock price index in the period of 2012 until 2016.Â  The purpose of this study was to find how the effect of inflation, BI rate, and dollar/rupiah rate on composite stock price index. In taking samples in this study using the method of documentation that is sampling research by using historical data. The sample of this study consists of 60 historical data that is monthly data from 2012-2016. Data analysis method in this research is multiple regression analysis.The result of this research shows that Inflation and Bi rate do not have influence to the change of value of Composite Stock Price Index but for Dollar / Rupiah Dollar variables have an effect to change of value of Composite Stock Price Index.Keywords: Composite Stock Price Index, Inflation, BI Rate, Dollar / Rupiah Rate.